2012
DOI: 10.1039/c2pp25187f
|View full text |Cite
|
Sign up to set email alerts
|

Phototherapeutic hardening modulates systemic cytokine levels in patients with polymorphic light eruption

Abstract: The etiopathogenesis of polymorphic light eruption (PLE) has been linked to impaired UV-immunosuppression, Langerhans cell (LC) retention, and an absence of neutrophil infiltration into UV-exposed PLE skin. We have previously shown that photohardening restores the impaired neutrophil responsiveness to the chemoattractants leucotriene B4 and formyl-methionyl-leucyl-phenylalanin in PLE patients. The aim of this study was to investigate whether photohardening modulates baseline chemokine and cytokine levels which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 62 publications
0
28
1
Order By: Relevance
“…While previous studies demonstrate that both keratinocytes and fibroblasts can produce proinflammatory cytokines upon stimulation (Ablett et al, 2003; Huleihel et al, 1993; Köck et al, 1990; Mustafa et al, 2000; Urbanski et al, 1990; Wolf et al, 2013), our results further suggest that the skin is likely an important contributor to the age-associated increase in serum inflammatory cytokines. While aged mice display elevated serum amyloid A and TNFα levels, mRNA levels of both amyloid A and TNFα increase only in the aged skin, but not in the liver, a putative source of serum amyloid A (Upragarin et al, 2005).…”
Section: Discussioncontrasting
confidence: 70%
“…While previous studies demonstrate that both keratinocytes and fibroblasts can produce proinflammatory cytokines upon stimulation (Ablett et al, 2003; Huleihel et al, 1993; Köck et al, 1990; Mustafa et al, 2000; Urbanski et al, 1990; Wolf et al, 2013), our results further suggest that the skin is likely an important contributor to the age-associated increase in serum inflammatory cytokines. While aged mice display elevated serum amyloid A and TNFα levels, mRNA levels of both amyloid A and TNFα increase only in the aged skin, but not in the liver, a putative source of serum amyloid A (Upragarin et al, 2005).…”
Section: Discussioncontrasting
confidence: 70%
“…Chronologically aged mice, with no clinical evidence of inflammation, exhibit cutaneous functional abnormalities, which are accompanied by elevated levels of certain cytokines in the skin and circulation . Pertinently, disruption of epidermal permeability barrier function by repeated tape‐stripping, and following acute exposure to erythemogenic UV‐B provoke increases in the levels of cutaneous and circulating cytokines, including IL‐1β, IL‐6 and TNFα …”
Section: Discussionmentioning
confidence: 57%
“…6 The induction of allergic contact sensitization against dinitrochlorobenzene following UV irradiation of the sensitization site was shown to occur significantly more frequently in patients with PLE than in healthy subjects. 11,22 In comparison with controls, we found that TGF-b1 expression in both PLE and CDLE was decreased by > 50%, indicating that both conditions are characterized by similar dysbalances in the number of Tregs and the cytokine network. However, the allergic contact response to dinitrochlorobenzene in previously sensitized patients with PLE and healthy subjects is gradually and equally suppressed by irradiation, also explaining the beneficial effect of UV hardening in patients with PLE.…”
Section: Discussionmentioning
confidence: 78%
“…20 As shown in previous studies, we observed that epidermal Langerhans cells are also significantly diminished in CDLE. [3][4][5]22 In skin lesions of patients with PLE, we have investigated Tregs and immunoregulatory factors such as TGF-b1, IL-10 and RANKL. 21 We observed significantly reduced levels of CD68+ cells in the epidermis of PLE lesions compared with CDLE and controls.…”
Section: Discussionmentioning
confidence: 99%